Studi Pendampingan Pengembangan Bahan Ajar Tematik Terintegrasi Literasi Baru dan Literasi Bencana Pada Guru IPA Kabupaten Agam - Asrizal Asrizal; Festiyed Festiyed (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Literacy is required in the 4.0 industrial revolution and education in Indonesia. However, the real condition indicated that the integration of literacy in science learning of the science teachers was still limited. The solution of this problem is assisting the partner in writing science thematic learning material by integrating new literacy and disaster literacy. The objective of assisting is to improve competency of science teachers in writing thematic learning material. The target of the assisting activity was the teachers in science MGMP in Agam district. Methods in assisting include presentation and discussion, group work, independent task, and task presentation. Instruments to collect the data consist of knowledge test and questionnaire. Data analysis techniques were descriptive statistical analysis and paired comparison test. There are four results of the assistance, namely: 1). The average value of skills in integrating new literacy into thematic science worksheet is 70.5 and this average value can be classified into good category, 2). Teachers felt the benefits of assistance in aspects of learning material, thematic learning, integration of new literacy and disaster literacy in learning, and writing of thematic learning material, 3). The response of student from to the use of thematic science worksheet by integrating new literacy can be entered into very good category with an average value of 86.7, and 4). The implementation of assisting on the writing of thematic science learning material is effective to improve the new literacy and disaster literacy of science teachers.